Industrial heritage in an era of climate catastrophe: Contamination as heritage - Thompson, Carolyn F. (Geographies of Post-Industrial Place, Memory, and Heritage, 2020)
The purpose of this chapter is to preliminarily explore the fruitfulness of understanding industrial heritage sites through the lens of environmental catastrophe in the 21st century. While geographers have been increasingly exploring heritage over the past few decades, concerned with its significance in terms of cultural and social representations, as well as an economic commodity, and industrial heritage has become more widely recognized as a key aspect of identity in the cities of the westernized world, research has overlooked the fascinating nexus between the industrial production marked in the sites of industrial heritage and the environmental outcomes of those processes. There is no concern more pressing in the present than the reality of climate change and environmental catastrophe and so this presentation considers exploring the interconnections between remembering the social and historical significance of industrial heritage sites and recognizing the ways these sites threaten our future. Through a preliminary case study of English Station, a disused power station on the Mill River in New Haven, Connecticut, I explore how this site represents the aspirations and progress of New Haven as an industrial, electrified, automobile city, as well as the current environmental catastrophes on our doorstep.
Keywords: dept.egm